Influencia del inadecuado cumplimiento de roles familiares en el bajo rendimiento escolar de los alumnos beneficiarios de la asociación civil amor en acción. distrito de huanchaco. 2013 - Zegarra Guerrero, Luz Emelina (2013)
This thesis was carried out with the purpose to analyze the influence of inadequate compliance with family roles in poor school performance of the student beneficiaries of the "Civil Association Love in Action" - District of Huanchaco. It has been considered the type of applied research, on the basis of an explanatory design, and the sample consisted of 46 children as beneficiaries, with which they work by applying the methods and techniques of quantitative and qualitative research. The results obtained, we can infer that there is neglect of the needs of the children (as) on the part of the father or the mother due because they prioritize other people or other work situations, family instability marked that they give rise to conflicts, situation that affects the poor school performance of the student beneficiaries of the "Civil Association Love in Action". Finally we believe that educational policies should be geared toward the incorporation of parents in the compliance of their roles for the integral formation of the learners.